Criminal Law Aspects in Product Counterfeiting Cases Against Industrial Design Protection - Mashendra Mashendra; Hayun Hayun; Hasiruddin Hasri; Ahmad Zein L Waru (Journal of Law Science, 2024)
The criminal law facets pertaining to instances of product counterfeiting are examined in this article within the framework of industrial design protection. An examination of the current legal structure pertaining to product counterfeiting and an investigation into the ramifications of criminal law on the protection of industrial designs are the objectives of this article. Additionally, this article examines the diverse legal frameworks and regulations that pertain to the preservation of industrial designs against counterfeit products in different jurisdictions. The applicable elements of criminal law, such as the penalties levied against counterfeiters, are the primary focus. Furthermore, the article delves into the obstacles encountered by law enforcement in regards to safeguarding industrial designs and preventing product counterfeiting. This study demonstrates that criminal law protection of industrial designs is a crucial component in the fight against counterfeit products. It is necessary to strengthen the legal framework, promote cross-border cooperation, and increase all stakeholders' awareness of the significance of industrial design protection